Comparisons of different treatment outcomes in IVF/ET patients with hydrosalpinx: a retrospective study - Beibei Bi; Xiao Han; Wei Dai; Lanlan Fang; Hao Shi; Linli Hu (Taylor & Francis Group, 2023)
Aims To explore suggestions for clinicians on the most effective treatment for hydrosalpinx undergoing IVF-ET.Materials and Methods We reviewed 936 women with hydrosalpinx and 6715 tubal infertile women without hydrosalpinx who underwent IVF/ICSI between January 2014 and August 2019 in our center. Hydrosalpinx patients received different treatments including laparoscopic surgery (only salpingectomy and proximal tubal occlusion/ligation were included), ultrasonic-guided aspiration and hysteroscopic tubal occlusion. Outcomes were analyzed by One-way ANOVA, Chi-Square test and logistic regression.Results The live birth rate (LBR) of laparoscopic surgery was significantly higher compared with hydrosalpinx aspiration (48.3% vs 39.6%, p = .024). The cumulative live birth rate (CLBR) of subsequent laparoscopic surgery was significantly higher compared with subsequent hysteroscopic occlusion (65.1% vs 34.1%, p = .001) and no subsequent treatment (65.1% vs 44.9%, p  <  .005). Subsequent laparoscopic surgery significantly improved the CLBR of hydrosalpinx patients who received ultrasonic-guided aspiration and didn't get clinical pregnancy in fresh cycles (Odds Ratio (OR) =1.875; 95%CI = 1.041-3.378, p = .036).Conclusions Laparoscopic surgery leads to significantly higher LBR than ultrasonic-guided aspiration and significantly higher CLBR than hysteroscopic occlusion and no treatment.